Perlindungan Hukum Bagi Tertanggung Atas Tindakan Agen yang Melanggar Asas Itikad Baik (Studi Kasus Agen PT Asuransi Jiwa Sinarmas MSIG (LIFE) - Radya Rafi Setyawan; Retno Wulansari (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
The focus of the author in writing this thesis is the case that occurred on the behavior of insurance agents PT Asuransi Jiwa Sinarmas MSIG (LIFE) with several insureds as victims of insurance policy forgery and will aim to answer the problem : First, the form of legal protection for the insured on the actions of agents who violate the principle of good faith. Second, the legal responsibility of the insurer for losses due to unlawful agent actions. The research method used is normative juridical, with the approach method namely doctrine, legislation and empirical cases. The legal materials used in this research are primary, secondary, and tertiary legal materials. The technique of collecting legal materials is by literature study by reviewing and studying legislation and case studies. The conclusion of the research shows : First, legal protection for the insured has actually been regulated in Article 16 Paragraph 3 POJK Number 69 / POJK.05 / 2016, Article 29 POJK Number 1 / POJK.07 / 2013 and Article 28 paragraph 7 of Law Number 40 of 2014 concerning Insurance which in the article protects the insured as a weak party and has the right to claim compensation. Second, the legal responsibility of the insurer, which is obliged to submit and comply with the legal process on the complaint of several insureds as Decision Number : 101/PDT/2023/PT MND and 92/PDT/2023/PT MND and Article 1367 Paragraphs 1 and 2 of the Civil Code.